Genetic base and coefficient of parentage of rice (Oryza sativa) varieties released in Kerala - SHIVKUMAR, SHIVKUMAR; RAO, L SUBBA; RAM, T; MAJUMDER, N D; PADMAVATHI, G; RAO, U PRASADA; KRISHNAIAH, K (The Indian Journal of Agricultural Sciences, 2013)
An examination of the pedigrees of 29 rice (Oryza Sativa L.) varieties of hybrid origin, released in Kerala during’ 1966-95, revealed a narrow genetic base, as only 37 ancestors were used directly or indirectly in their development Out of 37 ancestors, 10 ancestors contributed 74.14% of the genetic base, Similarly. the cytoplasmic diversity was also limited, as 41.38% varieties could be ’traced back maternally to the same ancestor ’Ptb 10’ (’Thekkancheera’) and’ thus probably carried its cYtoplasm, ’Dee Goo Woo Gen’ (DGWG) was the most frequently appeared ancestor (96,55%) due to its dwarling gene (sdl), All the ,29 varieties except ’Kayamkulam I’ were interrelated with an average coefficient of parentage of 0.137 for 406. combinations of 29 varieties.